Enterprise risk management (ERM) and its determinants: evidence from Malaysian public listed companies - Ahmad Rizal Razali
The increasing importance of managing risk together with the lack of empirical research in the Malaysian public listed companies, provide the main motivation for this study. Many researches have sought to examine Enterprise Risk Management (ERM) practices using primary data. However, researches using secondary data are still considered scarce. There are several advantages of using secondary data. Some of the advantages of using secondary data are: the figures are audited; accurate; and has been validated. In this study, the profiling, the extent of ERM practice and its determinants are examined for the Malaysian public listed companies. The profiling and the extent of ERM practice are done for 574 companies, for the period 2002-2007. The determinants of ERM on the other hand, are examined for 528 companies for 2007. Data is gathered from annual report of individual companies obtained from Malaysian Bourse and OSIRIS database. In this study, the profiling and the extent of ERM practice are done by industry, namely Industrial Products, Trading/ Services, Consumer Products, Properties, Constructions, Plantations, Infrastructure Projects, Technology, Hotels and Mining. For the determinants of ERM, Logit Regression analysis is employed with dummy ERM as the dependent variable. Chief Risk Officer, Leverage, Profitability, International Diversification, Majority Shareholder, Size and Turnover are used as independent variables. The results for the profiling indicate that the highest number of User (practice ERM) is Industrial Products (47). This isf followed by Trading/Services (45), Consumer Products (26), Properties (23), Constructions (13), Plantations (6), Infrastructure Projects (4), Technology (4), Hotels (1), and Mining (0). In terms of the extent of ERM practice, the results show that 169 companies (29 percent) adopt ERM practice while 405 companies (71 percent) do not. The results for the determinants of ERM suggest an appoinment of Chief Risk Officer, Turnover and International Diversification explain the determinants of ERM practice in the Malaysian public listed companies. That is, firstly, Turnover is positively and significantly related to ERM indicating that companies with higher turnover have higher possibility to adopt ERM practice. Secondly, Chief Risk Officer is positively and significantly related with ERM suggesting that companies having Chief Risk Officer are likely to support ERM programme. Finally, the dummy for International Diversification is negatively and significantly related to ERM indicating that companies that do not diversity their businesses internationally are likely to adopt ERM practice.